Formulasi Tepung Kacang Kedelai (Glycine Max) dan Tepung Umbi Garut (Maranta Arundinacea) pada Cookies sebagai Alternatif Makanan untuk Penderita Celiac Disease (Bebas Gluten) - Shephira Retri Pramudya; Esty Sukartini; Sudrajah Warajati Kisnawaty (Yayasan Literasi Sains Indonesia, 2026)
Celiac disease is an autoimmune disorder triggered by the consumption of gluten, a protein found in wheat, barley, and rye. Individuals with celiac disease must adhere to a strict gluten-free diet, as gluten intake can damage the intestinal villi, impair nutrient absorption, and increase the risk of malnutrition. This study aimed to evaluate the effect of formulation soybean flour (Glycine max) and arrowroot flour (Maranta arundinacea) on the characteristics of cookies as a gluten-free food alternative for individuals with celiac disease. The formulations used were F1 (20% soybean flour: 80% arrowroot flour), F2 (50%:50%), and F3 (70%:30%). The analyzed parameters included moisture content, color intensity (L*, a*, b*), and organoleptic attributes (color, aroma, taste, texture, and overall acceptance) assessed by 15 trained panelists. Data were analyzed using one-way ANOVA followed by LSD at a 95% confidence level. The results showed that the highest moisture content was found in F3 (5.58%), exceeding the SNI 2973-2018 standard (<5%). The color analysis indicated differences in brightness and yellowness among formulations: F1 tended to be brighter, F2 more reddish, and F3 more yellowish. The sensory evaluation revealed a significant difference in color preference among formulations (p = 0.023), with the highest score observed in F3. Meanwhile, aroma, taste, texture, and overall acceptance showed no significant differences (p > 0.05).